Inequality of Opportunity in Retirement Age – The Role of Physical Job Demands - Matthias Giesecke; Sarah Okoampah (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2014)
We quantify differences in the retirement age between manual and non-manual workers and evaluate these differences in the context of the literature on equality of opportunity. The focus is on the question how individual background during childhood transmits through physical demands of occupations on retirement ages. Individual retrospective data from the German Socio-Economic Panel are used to analyse labour force dynamics over the years 1984 to 2011. Discrete time duration models suggest that retirement ages differ substantially between manual and non-manual workers. To elaborate how such differences are explained by individual background characteristics on the one hand and effort and luck on the other hand, we make use of tests for stochastic dominance and a Blinder-Oaxaca decomposition. The result is that individual background characteristics explain a share of about one third of inequality in retirement ages as transmitted through physical demands of occupations. – – Wir quantifizieren die Differenz im Renteneintrittsalter zwischen Individuen, die sich hinsichtlich des Grades der physischen Arbeitsbelastung in ihrem Beruf unterscheiden. Diskrete Verweildauermodelle deuten auf substantielle Unterschiede im Renteneintrittsalter zwischen diesen Gruppen hin. Wir evaluieren die Differenz hinsichtlich der Frage, inwiefern prädeterminierte Umstände in der Kindheit über den Kanal der Selektion in physisch anspruchsvolle Berufe auf das Renteneintrittsalter wirken. Um Unterschiede zu separieren, die durch prädeterminierte Umstände auf der einen Seite und durch individuelle Entscheidungen oder Zufall auf der anderen Seite hervorgerufen wurden, testen wir auf stochastische Dominanz für ausgewählte prädeterminierte Kriterien und führen eine Blinder-Oaxaca-Zerlegung durch. Die Ergebnisse implizieren, dass prädeterminierte individuelle Charakteristika etwa ein Drittel der Differenz im Renteneintrittsalter erklären, welche über den Kanal des physischen Anspruchs der Beschäftigung transportiert wird.
Keywords: D63; J26; J62; C14; 330; retirement age; inequality of opportunity; physical job demands; blinder-oaxaca-decomposition